# If A – 1 = and , find (AB) – 1.

A – 1 = B = |B| = 1(3 – 0) – 2( – 1 – 0) – 2(2 – 0)

= 3 + 2 – 4

|B| = 1

Now, B – 1 = Cofactors of B are:

C11 = – 3 C21 = 2 C31 = 6

C12 = 1 C22 = 1 C32 = 2

C13 = 2 C23 = 2 C33 = 5

adj B = = So, adj B = Now, B – 1 = (AB) – 1 = B – 1 A – 1 = Hence, = Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Determinants of Matrices of different order59 mins  Determining a determinant63 mins  Lecture on Product of Determinants58 mins  Types of Matrices & Properties51 mins  Interactive Quiz on Properties of Determinants43 mins  Triangular Matrices & operations on matrices58 mins  Know About finding the Adjoint & Inverse Of Matrix46 mins  Test Yourself, Properties of Determinants30 mins  Interactive Quiz on Matrices & Determinants48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 